Mechanism of Photoactivation of Electron Transport in Intact Bryopsis Chloroplasts - Satoh, Kazuhiko (1982)
The mechanism of photoactivation of photosystem I electron transport was studied in intact Bryopsis corticulans chloroplasts. The evidence from chemical and photochemical studies suggests that photoactivation is a consequence of a reduction of an electron transport component, presumably ferredoxin-NADP(+) reductase. O(2) does not act as a mediator of the process but rather acts as an electron acceptor after photoactivation has occurred. We suggest that the initial function of the chloroplasts in a transition from dark to light is to initiate pseudocyclic electron flow.